Evaluation of Pre-Rigor Proteases Injections on Cooked Beef Volatiles at 1 Day and 21 Days Post-Mortem - Ma, Qianli (Auckland University of Technology, 2011)
The fact that tenderness plays a major role in consumer acceptance of meat has been known for many years. After appearance and tenderness, flavour is another important component influencing meat palatability. Although proteases are widely used in the meat industry to tenderize meat, they can also contribute to the formation of amino acids that act as precursors for volatile flavour formation in cooked meat. This research was carried out to determine the effects of pre-rigor injection of beef with nine proteases from plant and microbial sources, after 1 day and 21 days post-mortem storage, on the volatile profile of cooked beef using solid phase microextraction (SPME) in combination with gas chromatography (GC) and mass spectrometry (MS) analysis. The topside of beef was injected with papain (PA), bromelain (BA), actinidin (Ac), zingibain (ZI), Fungal 31 protease (F31), Fungal 60 protease (F60), bacterial protease (BA), kiwi fruit juice (KJ), and Asparagus protease (ASP). A non-injected control (C) treatment was also included. In this study, a total of 56 key volatile compounds were found in cooked pre-rigor beef meat injected with proteases at 1 day and 21 days post mortem storage. This included 23 aldehydes, 5 ketones, 3 furans, 8 nitrogen and sulphur compounds, 4 alkanes, 7 alcohols and 6 terpenes. Eleven volatile compounds including camphene, 1,8-cineole, terpineol, citronellol, citral, geraniol, geranial, α-curcumene, zingiberene, α-farnesene, and β-sesquiphellandrene, were only detected in meat treated with ZI at 1 day and 21 days post-mortem storage. 3-methylbutanal and benzaldehyde were significantly increased (p<0.05) in the KJ 21 days treated sample. Aldehydes were the main chemical compounds that significantly changed with protease treatments and post mortem storage. Benzaldehyde was significantly increased (p<0.05) only in F31 and ASP treated samples from 1 day to 21 days post-mortem storage. A significant increase (p<0.05) in 3-methylbutanal was observed in KJ, BA, BR and F31 treated samples at 21 days post-mortem storage. Treatments with BR, PA, ASP, AC, and KJ (except KJ 21 days) proteases underwent fewer changes in the volatile compounds leading to a flavour profile closer to that of the control beef sample.
Keywords: Volatile compounds; Beef; SPME